Table of Content - - (Journal of medical and pharmaceutical sciences, 2024)
Table of Content: 1. Hereditary blood diseases in Jeddah (Sickle Cell Anemia – Thalassemia) Amna Sami Jamal Al-Lail, Nadia Rafed Al-Obaidi 2. Medical Students’ Perceptions of Online Learning During the COVID-19 Pandemic, Kuwait University: A National Survey Amar Ali Alnaqi, Ali Jasim Buabbas, Nada Jalal Jaafar, Aminah Mohammed Alawadi, Hamza Mohammed Alshawaf 3. Ovarian Torsion in Pregnancy: A Case Report Yasmeen Hassan Albadrani